La lisière : un outil de la fabrique agriurbaine. Lecture francilienne - Claire Aragau; Monique Toublanc (Territoire en Mouvement)
Considered as a category of action in the field of urban planning, the edge is questioned on the basis of its supposed qualities as a tool for structuring the fringes of conurbations, capable of implementing new territorial projects in line with the agriurbanism movement. The concept of edge for the land-use planning is tested in the Paris area specifically in the territories labelled “agriurban territory” in the Île-de-France Region. Those territories work as stages upon wich some metropolitain scenarios are played researching into innovative combinations of town and country. The edge appears to be an effective tool- with an heuristic value- for the diagnostic phase of a project to understand the interactions between urban and rural fringes, to grasp the ways of living in those borders and the composite landscapes that result of these interactions. The edge gives rise to new procedures provided by the rural and urban actors meeting and the porosity of the codes of law, the Rural Code and the Urban Code. The edge renews the grammar of urban planning in the service of a reading of the hybridization of spaces.